WEB-BASED BACKEND SYSTEM FOR CRM AND ALUMNI TRACER STUDY - Syuby Alwi Akbar Attala; hesti Rian (POLITEKNIK LP3I JAKARTA, 2026)
English Language Programs (ELP) is an English course institution that still manages customer data, course history, payments, student attendance, and alumni data manually using paper-based documents such as student ledgers, attendance lists, and teaching reports. This condition causes difficulty in tracing customer history, the absence of a structured alumni database, and the lack of a tracer study mechanism to monitor graduates. This study designs and builds a web-based backend information system integrating Customer Relationship Management (CRM) and alumni tracer study management at ELP. The system was developed using PHP with the CodeIgniter framework, the Model-View-Controller (MVC) concept, and a MySQL database. The Waterfall method was applied, consisting of requirement analysis, system design, implementation, testing, and maintenance, with data collected through observation, interviews, and literature study. The result is a backend system capable of managing customer data, course registration, monthly payments, student attendance, teaching reports, alumni data, and tracer study forms, with access divided between Staff and Admin roles. Black Box Testing results show all features function according to requirements.